Digital affordances and teacher agency in the context of teaching Chinese as a second language during COVID-19. (April 2022) - Chen, Mengtian
Abstract: The outbreak of COVID-19 brought about novel digital affordances for second language (L2) teaching by moving all the universities in mainland China abruptly to emergency online schools in early 2020. This unprecedented educational situation prompted teachers to exert more teacher agency on classroom teaching, leading to more discussion on the ecology of L2 teaching in an exploratory online environment. To know more about the relationships between digital affordances and teacher agency during the pandemic, the present study tracked two teachers' reflection on their Chinese language instruction over the 2020 spring semester to investigate how they utilized the special affordances via their teacher agency in L2 remote teaching. Reflective interviews showed their implementation of teacher agency through the use of technologies in relation to their teaching beliefs and social contexts. Framing digital affordances and teacher agency in an ecological view strengthened the links between classroom dynamics and social environment, which also implied adaptable instructional practices and resilient professional trends for future L2 online education. Highlights: The COVID-19 pandemic brings new digital affordances for online classroom teaching. Teachers exert more teacher agency in exploratory online schooling. Reflective teaching highlights the ecology of digital affordance and teacher agency. Teaching behaviors emerge from interactions between affordances and teacher agency. Emergency remote courses demand more classroom dynamics with social contexts.